Composite scintillators based on single crystal grains Y₂SiO₅:Ce (YSO) and Y₃Al₅O₁₂:Ce (YAG) - Galunov, N.Z.; Gerasymov, Ia.V.; Gorbacheva, T.E.; Grinyov, B.V.; Karavaeva, N.L.; Khabuseva, S.U.; Krech, A.V.; Levchuk, L.G.; Martynenko, E.V.; Popov, V.F.; Sidletskiy, O.Ts.; Sorokin, P.V.; et al. (Вопросы атомной науки и техники, 2017)
Radiation-resistant composite scintillators based on grains of inorganic single crystals of the yttrium orthosilicate Y₂SiO₅:Ce and yttrium aluminium garnet Y₃Al₅5O₁₂:Ce were studied. The irradiation of the samples by KIPT 10 MeV electron Linac causes the dose rate of 1,500 Mrad/h or 0.1 Mrad/h when it is 9.2 MeV beam electrons or bremsstrahlung photons, respectively. We run the measurements of light transmittance, luminescence spectra and scintillation light outputs of a scintillator before and after irradiation. The paper presents and analyzes the results obtained for scintillators exposed to doses about 25 Mrad (the dose rate is 0.1 Mrad/h) and 150 Mrad (the dose rate is 1,500 Mrad/h). Досліджені на радіаційну стійкість композиційні сцинтилятори на основі гранул неорганічних монокристалів Y₂SiO₅:Ce та Y₃Al₅5O₁₂:Ce. Для отримання композиційних сцинтиляторів гранули були введено в діелектричну гель-композицію Sylgard-184. Зразки опромінювалися на електронному (10~МеВ) лінійному прискорювачі ХФТІ безпосередньо електронами пучка з енергією 9,2~МеВ (при потужності дози 1500~Мрад/год.) і гальмівними фотонами (при потужності дози 0,1~Мрад/год.). Значення пропускання світла, люмінесценції та світлового виходу вимірювалися до і після опромінення. Представлені та проаналізовані результати, отримані для сцинтиляторів, опромінених до доз 25~Мрад при темпі 0,1~Мрад/год. та 150~Мрад при темпі 1500~Мрад/год. Исследованы на радиационную стойкость композиционные сцинтилляторы на основе гранул неорганических монокристаллов Y₂SiO₅:Ce и Y₃Al₅5O₁₂:Ce. Для получения композиционного сцинтиллятора зерна были введены в диэлектрическую гель-композицию Sylgard-184. Образцы облучались на электронном (10~МэВ) линейном ускорителе ХФТИ непосредственно электронами пучка с энергией 9,2~МэВ (при мощности дозы 1500~Мрад/ч) и тормозными фотонами (при мощности дозы 0,1~Мрад/ч). Значения пропускания света, люминесценции и светового выхода измерялись до и после облучения. Представлены и проанализированы результаты, полученные для сцинтилляторов, облученных до доз 25~Мрад при темпе 0,1~Мрад/ч и 150~Мрад при темпе 1500~Мрад/ч.